THE EFFECT OF FRAUD DIAMOND AND TECHNOLOGY ON FRAUD TENDENCIES OF AUTOMOTIVE DEALERSHIPS EMPLOYEES IN MALANG - Pambudi, Kharisma Oktavian (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This research aims to analyse the effect of pressure, opportunity, rationalization, capability and technologyon the fraud tendency of employees. The population of this study is employees of automotive dealerships located in Malang City.Using a convenience sampling method, 60 respondents are selected as samples. The data analysis technique used in this research is the multiple linear regression analysis.The results of this research indicate that the pressure, opportunity, rationalization, capabilityand technology positively affects the fraud tendency of Malang automotive dealerships employees. This also shows that the fraud diamond and technology have an influence on the occurrence of fraud committed by employees of Malang automotive dealerships.Keywords: Pressure, Opportunity, rationalization, Capability, Technology and Tendency Of Fraud Employees